PROBLEMATIKA RENDAHNYA KEMAMPUAN LITERASI SISWADI SEKOLAH DASAR - Sri Dewi Nirmala (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the analysis of problems and factors caused by the low literacy skills of students, especially in elementary schools. The study described in this article used a descriptive analysis method based on qualitative data through the results of questionnaires, interviews, and observations. The study was conducted in six elementary schools thatimplemented the School Literacy Movement (GLS) in Sukabumi Regency West Java. The study also involved fourth-grade elementary students and their parents who are classified into three categories, namely students who have high, medium, and low Early Literacy Ability (KLA). The results of the study showed that the factors caused by the students’ low literacy skills were (1) the socio-economic conditions of the family, (2) communication and guidance to children at an early age, (3) communication and tutoring during the school period, (4) facilities/collection of reading books at home, (5) HP, computer, television facilities, (6) gender, (7) the relationship between family, school, and community, and (8) the use of strategies or models in learning toread. Based on these findings, it could be recommended that (1) the fulfillment of literacy support infrastructure, (2) intensive guidance, especially in reading activities at home, (3) increase of the GLS activities, and (4) use of reading learning models in the learning process in elementary schools.